الانحرافات السلوكية لدى طلبة المرحلة المتوسطة من وجهة نظر المدرسين والمدرسات (Journal of the College of Basic Education, 2023)
The current research aimed to identify behavioral deviations among middle school students . The current research is determined by middle school teachers, where a random sample of (150) male and female teachers was selected from the city of Baghdad. To achieve the objectives of the research, the researcher prepared a scale to measure behavioral deviations among middle school students The researcher used it to extract the results of the research It reached a set of results, and accordingly the researcher came out with conclusions, recommendations and suggestions.